Evaluation of the clinical and sociodemographic features of patients with vitiligo from the central region of Romania - Fekete, Laszlo; Fekete, Gyula Laszlo; Iantovics, Laszlo Barna; Fekete, Júlia Edit; Bacârea, Vladimir (Frontiers in Medicine, 2025)
BackgroundIn this study, we aimed to investigate and analyze the clinical and sociodemographic features and possible correlation with factors associated with the development of vitiligo in a cohort of patients suffering from this disease in the central region of Romania.MethodsPatients diagnosed with vitiligo from private outpatient clinics in the region and from the outpatient clinic of the Dermatology Clinic in Târgu Mureş participated in the study. The study period was between March 2021 and March 2022. Both sets of patients adhered to the same specified inclusion and exclusion criteria. Included just patients who received a complete dermatological clinical examination. They were asked by experienced physicians about epidemiological and clinical data of the disease, using the questions about vitiligo from the validated questionnaire edited by the Vitiligo Research Foundation from the United States of America. The patients who were given incomplete responses were excluded. This questionnaire contains 30 questions with multiple answers, about the patients with vitiligo, divided into seven subgroups as follows: group 1. Origins (demographic data), 2. History of vitiligo, 3. Vitiligo description, 4. Vitiligo treatments, 5. Skin condition, 6. Other conditions (comorbidities), 7. Impact (cost of treatments). Our study consisted of 114 patients, all of whom were Caucasians with Fitzpatrick skin types ranging from I–III.ResultsWe have analyzed the found data and compared the result with the data found in the literature. Most of the clinical and epidemiological characteristics of vitiligo in our patients were similar to those in other studies. A few of the characteristics linked to the possible appearance of the disease were present in higher percentages like the presence of the disease in the family, lighter color of the eyes, gray colored hair, the presence of the halo naevus, the predisposition to sunburn, the skin trauma as starting cause and the presence of increased level of thyroid disease.ConclusionBased on our results, we can conclude a profile of a potential patient who can develop vitiligo. To our knowledge, this study is the first of its kind from our country, however, our inferences remain limited by the single center, a relatively small sample size, recall bias, and a self-decided classification of some clinical aspects, which are potential limitations of this study.